ZnO nanowire sensitization with Ru polypyridyl complexes: charge-transfer probed by spectral and relaxation photocurrent measurements - Vega, Nadia Celeste (2018)
Dye-sensitized ZnO nanowire (NW) electrodes were fabricated using Ru polypyridyl complexes that use nitrile instead of carboxylic group as anchoring unit to the NW surfaces. The complexes formula is [Ru(bpy)3−x(Mebpy-CN)x]2+ (x = 1−3, bpy = 2,2'-bipyridine, Mebpy-CN = 4-methyl-2,2'-bipyridine-4'-carbonitrile). The ZnO NWs were grown by a vapor transport method on insulating SiO2/Si substrates. The sensitized ZnO NW electrodes were studied by electron microscopy, Raman and PL spectroscopies, and spectral and relaxation photocurrent measurements. The Raman spectra confirm that the complexes were effectively anchored to the ZnO NWs through one of the pendant nitrile groups of the bipyridyl ligands. The nanostructured morphology of the NW electrodes was maintained so that their light trapping characteristics were preserved. The Ru complexes were found to be excellent sensitizers of the ZnO NWs, improving by orders of magnitude their photocurrent in the visible region. The Fe-based complex of formula [Fe(Mebpy-CN)3](PF6)2 was also tested; however it did not show any sensitizing effect. An order of magnitude shortening of the persistent photocurrent relaxation times (after the illumination is interrupted) was found to occur upon successful sensitization of the ZnO NWs with the Ru complexes. This effect is interpreted in terms of hole traps at ~1 eV above the ZnO valence band edge, which are lowered by ~50–60 meV in the soaked samples due to screening of the trap centers provided by the extra photoexcited charge carriers transferred from the sensitizing complex to the NWs.